INVESTIGATING THE EFFECT OF CONSERVATION TECHNIQUES ON THE LAND DEGRADATION OF TROPICAL CATCHMENT PRONE TO LANDSLIDE - Christanto, Nugroho; Sartohadi, Junun; Setiawan, Muhammad Anggri; Hadi, M Pramono; Jetten, Victor G; Shrestha, Druba Phika (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Land degradation in Serayu watershed is a major concern in central Java and in Indonesia. As part of a broader effort to develop a land degradation assessment tool in tropical area, this study implemented a process-based watershed hydrology to assess the effect of conservation technique upon land degradation by using PCRaster. STARWARS was used to assess the watershed hydrology in the area based on their land use/ land cover, soil, and slope profiles. The results from STARWARS were used as inputs for the PROBSTAB model to simulate the slope stability in the area. DEM scenario were used, they are with terraces and without terraces.The models show that the landuse practice in the study area work like two edges of sword. The promoting of bench terrace can be reducing the risk of soil erosion but in the other hands it increases in the risk of landslide. From the slope-stability modeling, we can see that the terrace increases the pore-water pressure significantly which lead to the ideal conditions for the failures. The extremely high intensity rainfall, in the other hands, may build a sharp increase of pore-water pressure. The increasing probability of failure might cause the soil erosion even worse. Therefore, in order to make the terrace practice is effective to control the land degradation process; the terrace has to be well maintained.